External reference pricing and the choice of country baskets and pricing rules - Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
This paper models different external reference pricing schemes - a price cap based on the drug price in one or two countries and on the minimum or average drug price - in a three-country framework. It studies the choice of external reference pricing schemes in one country as well as its effect on welfare in the other countries, the manufacturers export decision, and the incentives for the other countries to also adopt an external reference pricing scheme. Depending on market size in the country adopting external reference pricing and market size difference of the other two countries, welfare is highest under the minimum price-rule or under the average price-rule. External reference pricing increases the drug price and decreases welfare in the other countries. If the market size in the country adopting an external reference pricing scheme is sufficiently large, the manufacturer does not export to the other countries. There is the incentive for the other countries also adopt external reference pricing.
Keywords: F12; I11; I18; 330; external reference pricing